A brush with death : an artist in the death camps - Wyszogrod, Morris, 1920- (State University of New York Press, 1999)
"In this memoir Morris Wyszogrod recounts his experiences from the time of the Nazi invasion of Poland to the liberation of the Theresienstadt concentration camp."
Includes index.
Keywords: Wyszogrod, Morris, -- 1920-; Pariser Friedenskonferenz -- 1919-1920 -- Paris -- Polish Delegation; Jews -- Poland -- Warsaw -- Biography.; Holocaust, Jewish (1939-1945) -- Poland -- Warsaw -- Personal narratives.; Holocaust, Jewish (1939-1945), in art.; Warsaw (Poland) -- Biography.; Juifs -- Pologne -- Varsovie -- Biographies.; Holocauste, 1939-1945 -- Pologne -- Varsovie -- Récits personnels.; Holocauste, 1939-1945, dans l'art.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Holocaust.; Holocaust, Jewish (1939-1945) in art; Jews; Poland -- Warsaw; Judenvernichtung; Künstler; 1939-1945; Autobiography; Personal Narrative; Biography; autobiographies (literary works); Autobiographies; Biographies; Personal narratives; Autobiographies.; Personal narratives.; Biographies.; Récits personnels.